Investigation of Physical Education and Sports School Students’ Anxiety to Catch COVID-19 - Ali Yıldırım, (Journal of Educational Issues, 2024)
This research was carried out to examine the anxiety to catch COVID-19 of students studying at School of Physical Education and Sports. The sample of the study consists of 209 students, 98 male and 111 female, studying at the School of Physical Education and Sports at Kilis 7 Aralik University. “Personal Information Form” and “Anxiety to Catch COVID-19 Scale” developed by Tekkurşun et al. (2020) were used as data collection tools. The data obtained in the research were analyzed using the IBM SPSS 25.0 program. As a statistical method in the analysis of the data, frequency analysis was used to determine the percentage distribution of personal information. T-Test and ANOVA test were used for independent groups, and the level of significance was considered as p < 0.05. According to the findings, it was observed that there was a statistically significant difference in favor of women in the individual anxiety sub-dimension in terms of the anxiety to catch COVID-19 based on the gender variable of the students (p < 0.05). There was no significant difference found in terms of the variables of the department they study, whether they do sports, their chronic disease conditions, and their grade levels (p > 0.05). As a result, it has been determined that while the anxiety to catch COVID-19 of the students studying at the Physical Education and Sports School is significantly higher in women, there is no significant difference in terms of the variables of the department they study, their chronic disease conditions, whether they do sports, and their grade levels.